The Influence of Digital Marketing Strategy and Brand Image on Consumer Purchase Intention at Warehouse Coffee Container in Panam, Pekanbaru - Akbar, Rahmad; Yetti, Dzulhijjah; Nurkholis, Nurkholis; Kaido, Boris; Febrianton, Adi (Journal of Engineering Science and Technology Management, 2025)
This study investigates the influence of digital marketing strategy and brand image on consumer purchase intention at Warehouse Coffee Container in Panam, Pekanbaru, where competition among coffee shops continues to intensify. Digital marketing has become a crucial channel to reach consumers, while brand image strongly shapes consumer perceptions and purchase behavior. A quantitative explanatory design was applied, with data collected from 120 consumers selected through purposive sampling. Questionnaires were distributed to measure perceptions of digital marketing strategy, brand image, and purchase intention. Data analysis was conducted using SPSS, employing validity and reliability tests, classical assumption tests, and multiple linear regression to test the proposed hypotheses. The results demonstrate three major findings: digital marketing strategy has a positive and significant effect on consumer purchase intention, brand image also positively and significantly influences purchase intention, and digital marketing strategy significantly enhances brand image. Furthermore, the joint influence of digital marketing strategy and brand image was found to be significant in determining purchase intention. This study provides both theoretical and practical contributions. Theoretically, it extends evidence on the role of marketing strategies in shaping consumer behavior within the food and beverage industry. Practically, it emphasizes that effective digital marketing combined with a consistent brand image can strengthen competitiveness, attract more consumers, and increase purchase intention in the highly competitive coffee shop market